Experimental evidence on the relationship between perceived ambiguity and likelihood insensitivity - Luca Henkel (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Observed individual behavior in the presence of ambiguity is characterized by insufficient responsiveness to changes in subjective likelihoods. Such likelihood insensitivity under ambiguity is integral to theoretical models and predictive of behavior in many important domains such as financial decision-making. However, there is little empirical evidence on its causes and determining factors. This paper investigates the role of beliefs in the form of ambiguity perception - the extent to which a decision-maker has difficulties assigning a single probability to each possible event - as a potential determinant. Using an experiment, I exogenously vary the degree of ambiguity while eliciting measures of likelihood insensitivity and ambiguity perception. The results provide strong support for an ambiguity perception based explanation of likelihood insensitivity. Not only are the two measures highly correlated on the individual level, but changes in ambiguity perception due to the exogenous variation also directly induce changes in likelihood insensitivity. My evidence thus substantiates the perception based interpretation of likelihood insensitivity brought forward by multiple prior models in contrast to preference based explanations of other commonly used models.
Keywords: D81; D83; D91; C91; 330; Ambiguity; decision-making under uncertainty; likelihood insensitivity; multiple prior models